Parental Attitudes toward Outdoor Nature Play: Challenges and Opportunities for Young Children in Malaysia - Sauli, Syaza Soraya; Wyver, Shirley; Mohd Kosnin, Azlina (Southeast Asia Early Childhood Journal, 2025)
Outdoor play in natural environments is vital for children’s holistic development, yet many parents may undervalue its importance, limiting opportunities for engagement with nature. This mixed-methods study examined Malaysian parents’ attitudes toward outdoor play and the barriers shaping children’s participation. Survey data were collected from 132 parents using a validated instrument (McFarland et al., 2011), complemented by semi-structured interviews with eight parents. Results indicated a modest but significant positive relationship between parents’ attitudes toward outdoor recreation and the time children spent outdoors, while general pro-nature attitudes showed no association. Interviews highlighted five recurring barriers: safety concerns, limited facilities, time constraints, urbanisation, and family dynamics. Collectively, these findings reveal a disconnect between parental awareness and actual practice. The study underscores the need for multifaceted strategies, including parental education, stronger school–family partnerships, and policy reforms, to better support outdoor play in nature. It offers practical implications for educators, policymakers, and caregivers seeking to foster active, healthy, and environmentally connected childhoods in Malaysia.